The Role of MSMES In Increasing Community Income: Penelitian - Yanthi Meitry Gunawan; Indah Kusumawat; Lena Erdawati; Ilma Darojat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Along with the significant economic development, people are required to be able to continue to exist in living the wheel of life, so they are required to have additional income to be able to meet their living needs, when the economy is difficult and job opportunities are getting narrower, there needs to be growth of MSMEs to be able to improve people's living standards, create a business environment that is able to encourage economic growth to increase people's income, with the growth of MSMEs it is hoped that people's income will also increase.